Asymmetric gating of a homopentameric ion channel GLIC revealed by cryo-EM - Zhuowen Li; Nikhil Bharambe; Kashmiri Manishrao Lande; Bjarne Feddersen; Asha Manikkoth Balakrishna; Philip C. Biggin; Giriraj Sahu; Sandip Basak (Proceedings of the National Academy of Sciences, 2025)
Pentameric ligand-gated ion channels (pLGICs) are vital neurotransmitter receptors that are key therapeutic targets for neurological disorders. Although the high-resolution structures of these channels have been elucidated, capturing their dynamic conformational transitions remains challenging due to the transient nature of intermediate states. In this study, we investigated a prokaryotic proton-gated pLGIC, GLIC. In our cryo-EM data at pH 4.0, we identified and segregated asymmetric particles, which we precisely aligned to resolve high-resolution structures of several previously unresolved asymmetric intermediate states, in addition to symmetric closed and open states. Detailed structural analysis revealed systematic conformational changes at individual subunits driving the channel opening. Molecular dynamics simulations were used to assign the functional states. We further examined the roles of the F116 and Y251 residues, located at the domain interface, playing a central role in interdomain communication. In addition, patch-clamp experiments on GLIC I240A and L241A mutants, located in the M2 helix, demonstrated their importance in channel gating. Together, these results shed light on the sequential and asymmetric conformational transitions that occur during GLIC activation, offering a deeper mechanistic understanding of asymmetric gating in pLGICs.